The Galileo Commission Towards a post-materialist science. An invitation to look through the telescope - Lorimer, David 1952- (2019)
This article provides an account of the rationale behind the establishment of the Galileo Commission and its recently published report.
Keywords: Galileo commission; consciousness revolution; scientific and medical network; scientific methodology; Scientism